The rise of mindfulness and its resonance with the Islamic tradition - Thomas, Justin (Mental health, religion & culture, 2017)
Mindfulness-based interventions have grown in prominence over the past decade. Evidence of their efficacy has been an important driver of their widespread acceptance and proliferation. Although secularised, these mindfulness-based interventions are derived from and influenced by Eastern spiritual traditions, particularly Buddhism. For this reason, there is a need to explore the acceptability of such approaches among individuals firmly committed to theistic traditions such as Judaism, Christianity and Islam. This article examines the rise of mindfulness-based interventions, exploring the sparse literature concerning the acceptability of such approaches among individuals with theistic perspectives divergent from both secular worldviews and Buddhist narratives. Finally, the article proposes several bridging concepts that might help practitioners of mindfulness-based approaches communicate key aspects of these interventions in a manner more culturally attuned and religiously resonant with the worldviews of Muslim clients.